Emerging treatment approaches in acute lymphoblastic and acute myeloid leukemias - Thomas X (Dove Medical Press, 2012)
Xavier ThomasHospices Civils de Lyon, Centre Hospitalier Lyon-Sud, Service d'Hématologie Clinique, Pavillon Marcel Bérard, Bât.1G, Pierre Bénite, FranceAbstract: The choice of treatment approach in acute leukemia depends on well-established prognostic factors. A number of features can predict the outcome of treatment including cytogenetics and an increasing list of molecular features. These are increasingly being used to direct postinduction therapy and support risk-adapted treatments that should achieve optimal results while minimizing nonrelapse mortality. In addition, they are also molecular targets for a new generation of small molecule inhibitors that are in early development and promise to further improve outcomes in the coming decade.Keywords: acute myeloid leukemia, acute lymphoblastic leukemia, treatment, targeted therapy